An In-Depth Study of Mobile Computing Devices Applications and Challenges - Rajeswari, A (International Journal of Computer Sciences and Engineering, 2025)
The mobile computing is a computing organization in which a computer and all necessary accessories like files and software are taken outto the field. It is a system of computing through which it is being able to use a computing device even when someone being mobile and therefore changing location. The portability is one of the important aspects of mobile computing. The mobile phones are being used to gather scientific data from remote and isolated places that could not be possible to retrieve by other means. The expertsaremakingtoproceduremobiledevicesand web-based applications to scientifically explore interesting scientific aspects of their surroundings, ranging from climate change, environmental pollution to earthquake monitoring.Thismobilerevolutionempowersnew ideas and innovations to spread out more speedily andefficiently. Herewewilldiscussinbriefabout the mobile computing technology, its guessing, challenges and theapplications.